Sportfunktionäre und jüdische Differenz. Zwischen Anerkennung und Antisemitismus – Wien 1918 bis 1938 - Hachleitner, Bernhard 1968- (De Gruyter, 2019)
Based on information about more than 600 Viennese Jewish officials, the book examines issues related to the self-characterization and outside characterization of Jews in Vienna. Sports are an important part of urban identity politics, providing a multifaceted image of engagement with Jewish “difference.” The study focuses on mass consumption sports, especially football, but includes swimming, boxing, and workers’ sports